Rasionalisme Sebagai Dasar Ilmu Pengetahuan dan Pendidikan dalam Islam - Alfadhilah, Jauharotina (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2024)
Abstract: Rationalism is one of the concepts in philosophy, which states that obtaining and disseminating knowledge, is an important thing that needs to exist with reason and ratio. Rationalism believes that the way to acquire knowledge is to rely on logic and intelligence. This study aims to examine the philosophy underlying the emergence of science. This research uses a type of literature research approach or literature study. Man uses his mind to understand and discover knowledge. It is also the main argument of rationalists who believe that truth cannot be based on lies, because truth lies in man's reason, God gives man what he wants, and no one can create lies. Rationalism is a way of thinking that considers reason and rationality as the source of all knowledge. Islam also calls on people to always use their intellect and think. This is what makes rationalism one of the foundations of science in Islam. The Islamic way of thinking that cannot be separated from the influence of revelation makes it interesting to study when the philosophy of rationalism seeks to obtain fundamental truths that focus on the relationship that gives rise to reason and science alone.